An Intelligent Algorithm of Operation and Maintenance Cost Based on BIM of the Utility Tunnel. Issue 3 (April 2021) - Wen, Zhongjun; Zhou, Wenyong; Zhao, Yijng; Zhao, Lin
Abstract: Through analyzing the relationship among the utility tunnel components, disaster risks and cost and the importance of BIM technology to integrated component information, disaster risk information and cost information, a component-disaster-cost data model based on BIM technology is built to realize dynamic recording of operation and maintenance cost and structured storage of operation and maintenance cost data. Based on the cost data model, the data flow of operation and maintenance cost analysis is established, artificial intelligence algorithm is introduced, deep learning, data analysis iteration is carried out, decision-making is assisted, and the healthy development of intelligent pipe gallery construction is promoted.